Optical microscopy for imaging airway epithelial functions - Li, Yingchen (Nanyang Technological University, 2021)
As the first line of defence against pathogens, Mucociliary Transport (MCT) is usually the first to be compromised when respiratory diseases occur. Hence, it is crucial that the Mucociliary Transport needs to be studied to lend a glimpse into the airway epithelial functions. In the context of Covid-19, the findings in this project may help provide means to diagnose and combat this pandemic, which further underscores the importance of this project. However, although microscopic images of the interior of airways can be taken with state-of-art technology, there are currently no methods to analyse the flowing speed of mucus in the airways automatically. Calculating the flowing rate of mucus is still a primarily manual task, which is time-consuming and requires close attention. As a result, it is highly imperative that an automatic algorithm that measures the flowing characteristics of the MCT and reflects them to the end-user needs to be developed. In this project, a functional set of algorithms that can measure the overall vertical and horizontal shift between two mucus images in the trachea is developed using MATLAB. These shifts are a good representation of the moving rate of the mucus. Besides, additional functions such as calculating the overall speed of mucus and measuring the flowing rate of mucus in a specified Region of Interest (ROI) have been implemented. The functions are integrated into a Graphic User Interface (GUI) that evolves into a standalone application to facilitate the end user’s usage. Results obtained via this algorithm have commendable accuracy and efficiency compared to results obtained from manual measurement and computation.